Intermittent Exotropia of the Divergence Excess Type. - Cooper, Jeffrey (Optometry & Visual Performance, 2018)
Intermittent exotropia of the divergence excess type is a unique strabismus with characteristic sensorimotor findings, symptoms and etiology. This paper reviews the most salient findings and incorporates these findings into a theory of etiology. Based upon etiology, a treatment regimen is presented which is consistent with clinical findings.